All-in-one hybrid tribo/piezoelectric nanogenerator with the point contact and its adjustable charge transfer by ferroelectric polarization. Issue 18 (15th December 2020) - Zhu, Quanyong; Dong, Le; Zhang, Jiawei; Xu, Kaixin; Zhang, Yaju; Shi, Huijie; Lu, Haowei; Wu, Yonghui; Zheng, Haiwu; Wang, Zifa
Abstract: The hybridization of tribo/piezoelectric nanogenerators (TPENG) has been verified as an efficient energy harvesting technique that utilizes both piezoelectric and triboelectric effects. Herein, we demonstrated a hybrid nanogenerator with a novel design of point contact that combined a BaTiO3 (BTO)-based piezoelectric nanogenerator and a two-terminal triboelectric nanogenerator to make both piezoelectric and triboelectric effects appear during one successive cycle. In TPENG, BTO ceramic sheet and commercial PTFE film were selected as the piezoelectric and triboelectric layer, respectively. A small hole was created through the PTFE film, which acted as a conductive channel to transport piezoelectric charges. The unique structure facilitates the study of the interaction between triboelectric and piezoelectric charges by adjusting the direction of ferroelectric polarization of the BTO. The TPENG can generate a maximum voltage of 45 V and a current density of 10.4 μA/cm 2 under an operating frequency of 2 Hz. The V-Q plot is employed to investigate triboelectric and piezoelectric effects from the perspective of output electrical energy, signifying that there is merely superposition of triboelectric and piezoelectric effect and no coupling between the triboelectric and piezoelectric charges for the TPENG with the point contact. The numerical analysis conducted by finite element simulation is consistent with the experimental results, demonstrating the rationality of the current experimental design. This work not only renders new insights into the understanding of piezoelectric and triboelectric effects in TPENG but also broadens the application prospects of Lead-free piezoelectric ceramics in energy conversion.